IMPLEMENTASI CONTINUOUS IMPROVEMENT DENGAN MENGGUNAKAN METODE PDCA PADA PROSES HANDOVER DI WAREHOUSE PT. ABC - Tri Widodo; Ismail Fardiansyah (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2019)
Culture of continuous improvement are favorite things that implemented in many business. This is also as concern in PT.ABC to apply continuous improvement in their operations. They use PDCA (Plan, DO, Check, Action) methodologies to solve the problem. One of PDCA case study that to be a topic for this research are problem solving in handover process.Lead time for handover process are 20 hours, it will be bring another negative effect. So, problem solving by using PDCA methodologies are conducted. Plan phase are problem Identification, identify cause, and developing solution by using some tools :swim lane flowchart, cause effect diagram, mind mapping effort and benefit matrix. Do phase are execute the action plan, then Check phase are verify the result. The last phase are Action, it is a standardization and next improvement topic .Outcome of PDCA implementing in handover process are reducing lead time in handover process, from 1.161 minutes to 265 minutes, or lead time decreasing by 77%. Other positive effect of PDCA implementing are facilitate the operator to operate the documents, utilize the space that caused by inventory reducing in staging area.Key words : PDCA, Swim lane, Cause and effect diagram, Mind mapping, Effort & benefit diagram.